Method for preparing immobilized enzyme by utilizing nano composite hydrogel and application of immobilized enzyme
Through nanocomposite hydrogel technology, calcium chloride and magnesium chloride are used to form nanoparticles and combined with polyhydroxyethyl methacrylate hydrogel, the enzyme loading rate and stability problems in traditional enzyme immobilization methods are solved, and the enzyme loading rate and stability problems are achieved. Efficient enzyme immobilization and catalytic activity improvement.
Patent Information
- Application Number
- CN202411508746.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional enzyme immobilization methods have problems such as weak adsorption, easy enzyme escape, crosslinking agent destroys the enzyme structure, and complex reaction conditions, resulting in low enzyme loading and catalytic performance, making it difficult to use stably in an industrial environment.
Using nanocomposite hydrogel technology, nanoparticles are formed through calcium chloride and magnesium chloride, combined with polyhydroxyethyl methacrylate hydrogel, and adsorption and cross-linking are used to utilize the isoelectric point difference between enzymes and carriers to form porous structures to improve Enzyme loading and stability.
It significantly improves the load and catalytic activity of the enzyme, enhances the stability of the enzyme, solves the problem of easy enzyme leakage, and simplifies the reaction conditions, ensuring the activity and structural integrity of the enzyme.
Smart Images

Figure BDA0005104820510000071 
Figure BDA0005104820510000081 
Figure BDA0005104820510000082
Abstract
Description
(I) Technical field
[0001] The invention belongs to the technical field of enzyme immobilization, and specifically relates to a method for preparing immobilized enzyme by utilizing nano composite hydrogel and application thereof. (II) Background technology
[0002] Enzymes are important macromolecules involved in biological life activities and are natural catalysts that participate in metabolic processes in the human body and maintain physiological functions. Enzymes have good selectivity and catalytic efficiency for substrates. The active center of the enzyme is formed by the folding of a three-dimensional peptide chain, and this structure responds quickly to changes in external conditions. Enzymes are widely used in bioengineering, food, medicine, chemical industry, environmental protection and other fields.
[0003] Alcohol compounds are important pharmaceutical intermediates. Common pharmaceutical intermediates include aliphatic alcohols, aromatic alcohols, alicyclic alcohols, ether alcohols and polyhydroxy alcohols. Enzyme catalysis has become an important technology for drug production. Enzyme catalysis can be used to synthesize alcohol pharmaceutical intermediates in a green and efficient manner, including statins (atorvastatin, rosuvastatin, pitavastatin), ticagrelor, aprepitant, etc. These alcohol pharmaceutical intermediates play an important role in drug synthesis and research and development. Through their synthesis or combination with other compounds, drugs can be given specific functions, such as improving biological activity, drug stability and solubility.
[0004] The use of free cells or enzymes as catalysts often has problems such as poor stability and easy inactivation due to volatility. Moreover, free cells or enzymes can usually only be used in one batch, resulting in a high proportion of enzyme preparations in the production cost. Enzyme immobilization may change the spatial structure outside the catalytic active center of the enzyme through interaction with the immobilized material, thereby improving the stability of the enzyme in an industrial environment, and also facilitating the separation of target products from the reaction system and the recovery of enzyme preparations. More importantly, immobilized enzymes can be used to construct continuous reactions, improve the catalytic performance of the enzyme and the space-time yield of the process, and reduce production costs. Thanks to a series of technical advantages of immobilized enzymes, they are widely used in the fields of medicine, food, water treatment, etc.
[0005] Traditional immobilization methods have certain defects, for example: the adsorption method has weak force and the enzyme is easy to escape, the encapsulation method is easy to leak, the cross-linking agent used in the cross-linking method will destroy the structure of the enzyme and cause the enzyme activity to decrease, and the reaction conditions in the covalent binding method are complex and will change the structure of the enzyme and affect the activity of the enzyme. Therefore, designing and synthesizing immobilization materials with industrial properties and improving the loading rate and catalytic performance of the enzyme in the carrier have become the research focus of the continuous synthesis of immobilized enzymes of alcohol pharmaceutical intermediates. (III) Summary of the invention
[0006] The present invention aims to provide a method and application of preparing immobilized enzyme by using nanocomposite hydrogel, using synthesized nanoparticles of magnesium calcium carbonate (MgCa(CO3 ) 2 ) is used as an enzyme carrier, and the difference in isoelectric points between the enzyme and the carrier is utilized. Under certain conditions, the enzyme and the carrier are given opposite charges, and the two are adsorbed on each other. The enzyme-adsorbed carrier is then converted into a hydrogel through the polymerization of poly(hydroxyethyl methacrylate) (pHEMA) hydrogel. The encapsulation method and the adsorption method are combined to enhance the enzyme immobilization force. The reaction conditions are mild and easy to operate, which effectively solves the problem of easy leakage of the enzyme load.
[0007] The technical solution adopted by the present invention is:
[0008] The present invention provides a method for preparing an immobilized enzyme using a nanocomposite hydrogel, the method comprising the following steps:
[0009] (1) Calcium chloride (CaCl 2 ) aqueous solution and magnesium chloride (MgCl 2 ) aqueous solution, and stirred at 20-30° C. and 300-600 rpm for 30 min (preferably 25° C. and 500 rpm for 30 min) under the action of a magnetic stirrer to obtain a nanoparticle mixture;
[0010] (2) adding an initiator and a monomer to the nanoparticle mixture, and then adding deionized water, and magnetically stirring at 20 to 30° C. and 200 to 400 rpm for 10 to 30 min (preferably at room temperature and 300 rpm for 20 min) to obtain a hydrogel prepolymer mixture; the initiator comprises 2-hydroxyethyl methacrylate; and the monomer comprises N-vinyl pyrrolidone;
[0011] (3) At room temperature, adding enzyme solution to the hydrogel prepolymer mixture, and then adding ammonium persulfate, cross-linking at 20-35° C. and 300-600 rpm for 1-100 min to obtain an enzyme-loaded nanocomposite hydrogel, and freeze-drying at -80° C. for 12 h to obtain a nanocomposite hydrogel immobilized enzyme.
[0012] Furthermore, in step (1), calcium chloride and magnesium chloride are respectively dissolved in deionized water and mixed to prepare an aqueous solution with a mass fraction of 5%; the calcium chloride aqueous solution and the magnesium chloride aqueous solution are mixed in a volume ratio of 1:1.
[0013] Furthermore, in the step (2), the final concentration of the initiator in the hydrogel prepolymerization mixture is 0.05-0.5 M (preferably 0.1 M), and the final concentration of the monomer is 0.1-1.0 mM (preferably 6.08×10 -2 M).
[0014] Furthermore, the enzyme solution in step (3) includes pure enzyme solution of carbonyl reductase or pure enzyme solution of lipase; more preferably, the amount of pure enzyme solution is 1 to 6 g / L in terms of protein content, and more preferably 2 g / L. The amino acid sequences of the carbonyl reductase and lipase are not limited, and pure enzyme solutions of carbonyl reductase or lipase known in the art after expression and purification by engineered bacteria can be used in the method of the present invention.
[0015] Furthermore, the concentration of ammonium persulfate added is 3-10 mg / mL (preferably 10 mg / mL) based on the volume of the hydrogel prepolymerization mixed solution.
[0016] Furthermore, step (3) cross-linking was performed at 25° C. and 500 rpm for 45 min.
[0017] The present invention also provides an application of an immobilized enzyme prepared by the method in catalyzing ketone compounds or ester compounds to prepare drug intermediates.
[0018] Furthermore, the method for preparing a drug intermediate by catalyzing a ketone compound using the immobilized enzyme is as follows: a nanocomposite hydrogel immobilized enzyme containing a carbonyl reductase is used as a catalyst, a ketone compound is used as a substrate, isopropanol is used as a cosubstrate, NADPH is used as a coenzyme, and a buffer solution with a pH of 3.0 to 10.0 is used as a reaction medium to form a conversion system, and the reaction is carried out at 30-80° C. (preferably 35° C.) and 1000 rpm. After the reaction is completed, the reaction solution is extracted, separated and purified using ethyl acetate to obtain a chiral aromatic alcohol; the ketone compound is 2-chloro-1-(3,4-difluorophenyl)ethanone, and the corresponding chiral aromatic alcohol is (1S)-2-chloro-1-(3,4-difluorophenyl)ethanol; the reaction medium is preferably a 0.1M, pH 6.0 citric acid buffer solution; the final concentration of the substrate is 15 g / L, the final volume concentration of isopropanol is 40%, the final concentration of NADPH added is 20 mM, and the final concentration of the catalyst added is 6 g / L.
[0019] Furthermore, the method for preparing a drug intermediate by catalyzing an ester compound using the immobilized enzyme is as follows: a nanocomposite hydrogel immobilized enzyme containing lipase is used as a catalyst, an ester compound is used as a substrate, and a buffer solution with a pH of 3.0 to 11.0 is used as a reaction medium to form a conversion system, and the reaction is carried out at 20 to 60° C. (preferably 35° C.) and 1000 rpm; the ester compound is p-nitrophenyl phosphate, and the corresponding product is p-nitrophenol; the reaction medium is preferably a 0.1 M, pH 6.0 citric acid buffer solution; the final concentration of the substrate is 30 g / L, and the final concentration of the catalyst is 12 g / L.
[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0021] (1) The method of the present invention increases the enzyme loading capacity. The present invention uses a composite hydrogel to immobilize the enzyme, and through the charge effect, the negatively charged enzyme protein is enriched on the positively charged nanoparticle carrier, thereby increasing the physical force, and through the in situ polymerization method, a three-dimensional network structure is formed to immobilize the carbonyl reductase or lipase inside the hydrogel, thereby increasing the pore volume, specific surface area, average pore size and pore width of the immobilized enzyme, thereby increasing the enzyme loading capacity, and the maximum loading rate is 3422 mg / g, which solves the problem of easy leakage of the immobilized enzyme by the embedding method.
[0022] (2) The reaction conditions of the method of the present invention are mild. The composite nano-hydrogel prepared by the cross-linking method of the present invention does not require deoxygenation and heating, and the operation process is simple. The reaction process is carried out in the aqueous phase, and no other solvents other than initiators and cross-linking agents need to be added. The reaction conditions are mild, and the three-dimensional conformation and activity of the immobilized enzyme (such as carbonyl reductase and lipase) are slightly affected, the activity of the enzyme is guaranteed, and the reaction time only needs 45 minutes, which is easy to control.
[0023] (3) The method of the present invention improves the stability of the immobilized enzyme. 2 The adsorption and desorption experiments verified that the immobilized enzyme prepared by the method of the present invention has a stable structure, and the morphology and pore size are controllable, and presents a porous structure. After the immobilized enzyme prepared by the present invention is reused for 10 batches, the enzyme activity still maintains most of the activity (>60%), showing good stability, and the immobilized enzyme can be prepared in batches, which has a good market application prospect.
[0024] (4) The immobilized enzyme prepared by the method of the present invention has a high catalytic activity. The immobilized enzyme prepared by the method of the present invention has a porous structure, which makes it easier for substrate molecules to enter the active site of the enzyme, not only reducing the mass transfer limitation, but also improving the catalytic efficiency, and having a high catalytic activity. After 10 batches, the specific activity of the immobilized enzyme can still reach 60% to 70% of the initial one. (IV) Description of the drawings
[0025] Figure 1 Schematic diagram of the principle of preparing immobilized enzymes using nanocomposite hydrogels.
[0026] Figure 2 Schematic diagram of the catalytic reaction for preparing immobilized enzyme using nanocomposite hydrogel.
[0027] Figure 3 This is a bar graph showing the effect of different immobilization materials on the maximum adsorption capacity of the enzyme in Example 7.
[0028] Figure 4 This is a curve diagram of the particle size (nm) and density (Int.Wt.Dff) of the immobilized enzyme in Example 8.
[0029] Figure 5 This is the adsorption equilibrium isotherm of the immobilized enzyme in Example 8.
[0030] Figure 6 This is a bar graph showing the specific surface area and porosity of the immobilized enzyme in Example 8.
[0031] Figure 7 This is a curve showing the effect of time on the carbonyl reductase loading in Example 3-5.
[0032] Figure 8 This is the effect curve of time on the lipase loading amount of Example 3-5.
[0033] Fig. 9 The effect of temperature on the enzyme activity of the immobilized carbonyl reductase prepared in Example 5 is shown in FIG.
[0034] Fig.10 The effect of temperature on the enzyme activity of the immobilized lipase prepared in Example 5.
[0035] Fig.11 The effect of pH on the enzymatic activity of the immobilized carbonyl reductase prepared in Example 5 is shown in FIG.
[0036] Fig.12 The effect of pH on the enzymatic activity of the immobilized lipase prepared in Example 5.
[0037] Fig.13 The effect of the number of uses on the enzyme activity of the immobilized carbonyl reductase prepared in Example 5.
[0038] Fig.14 The effect of the number of uses on the enzymatic activity of the immobilized lipase prepared in Example 5.
[0039] Fig.15 FTIR spectra of the immobilized carbonyl reductase prepared in Example 5 after different number of cycles. (V) Specific implementation methods
[0040] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0041] In the following examples, unless otherwise specified, raw materials, reagents or processing techniques are all conventional commercial products or conventional processing techniques in the art.
[0042] The pure enzyme solution of carbonyl reductase used in the present invention is prepared by referring to the method of Example 3 of Chinese invention patent CN116410946A to prepare LsCR M6 Purified enzyme, enzyme protein concentration 5.4g / L.
[0043] The lipase PAE pure enzyme solution was prepared by referring to the method of Example 1 of Chinese invention patent CN113667704A, and the protein concentration was 2.3 g / L.
[0044] Example 1: Silica-immobilized enzyme
[0045] 1. Silicon dioxide (SiO 2 ) Carrier: Weigh 0.11g of hexadecylpyridine chloride and 0.7g of polyacrylic acid, add them to 100mL of deionized water and stir vigorously. After the solution is mixed evenly, add 0.8g of 25% ammonia water. After stirring for 20 minutes, add 0.53g of propyl orthosilicate, continue stirring for 30 minutes, transfer the mixture to a high-pressure reactor, and place it at 80°C for reaction for 48 hours. The obtained product is centrifuged, washed with deionized water, and dried at 60°C. The obtained white powder is placed in a muffle furnace and calcined at 550°C for 5 hours to remove the organic template, and 0.6g of silicon dioxide (SiO 2 ) carrier.
[0046] 2. Immobilized carbonyl reductase LsCR M6 : 5 mg of SiO prepared in step 1 2 The sample was dispersed in 10 mL of carbonyl reductase LsCR M6 The pure enzyme solution was shaken and adsorbed on a shaker at 120 rpm and 25°C for 24 h. The resulting mixture was centrifuged at 12000 r / min for 5 min in a high-speed refrigerated centrifuge, the supernatant was discarded, and the precipitate was washed twice with pH 7.0, 0.05 M phosphate buffer and centrifuged to collect the precipitate to obtain 7 mg of immobilized carbonyl reductase LsCR M6 ,stand-by.
[0047] 3. Immobilized lipase PAE: 5 mg of SiO prepared in step 1 2 The sample was dispersed in 10 mL of pure lipase PAE enzyme solution and adsorbed on a shaker at 120 rpm and 25°C for 24 h. The resulting mixture was centrifuged at 12000 r / min for 5 min in a high-speed refrigerated centrifuge, the supernatant was discarded, the precipitate was washed twice with pH 7.0, 0.05 M phosphate buffer and centrifuged, and the precipitate was collected to obtain 7.2 mg of immobilized lipase PAE for later use.
[0048] Example 2: Lecithin liposome-immobilized enzyme
[0049] 1. Immobilized carbonyl reductase LsCR M6 : Weigh 73.7 mg of 2-oleoyl-1-palmitin glycerol-3-phosphocholine and 0.5 mg of didodecyl dimethyl ammonium bromide, dissolve in 20 mL of a 1:1 chloroform-methanol mixed solution, record as mixed solution 1. Take 1.0 mL of carbonyl reductase LsCR M6The pure enzyme solution was dissolved in 1.0 mL of a mixed solution of ammonia and methanol in a volume ratio of 1:5, which was recorded as mixed solution 2. Then, mixed solution 1 and mixed solution 2 were mixed in a 50-mL round-bottom flask, and vacuum rotary evaporated at 60 rpm in a 45°C water bath for 1 h to form a uniform film. 5 mL of PBS buffer (pH 7.4) was added to the surface of the film, and hydrated at 60 rpm in a 65°C water bath for 2 h. During the hydration period, an ultrasonic device (150 W) was used to sonicate 4 times, each time for 1 min, to obtain a milky white milk-like liposome suspension. Centrifuged at 15,000 rpm and 4°C for 1 h to remove the unencapsulated free enzyme. Carbonyl reductase LsCR was obtained by extrusion through a 200 nm polycarbonate membrane 6 times. M6 500 mg of liposomes with immobilized enzyme.
[0050] 2. Immobilized lipase PAE: Immobilize the carbonyl reductase LsCR in step 1 M6 The pure enzyme solution was replaced with an equal amount of pure lipase PAE enzyme solution, and other operations were the same to obtain 500 mg of lipase PAE immobilized enzyme liposomes.
[0051] Example 3: Nanoparticle-immobilized enzyme
[0052] 1. Immobilized carbonyl reductase LsCR M6 Calcium chloride (CaCl 2 ), magnesium chloride (MgCl 2 ) were dissolved in deionized water and mixed to prepare a 5% aqueous solution. The calcium chloride aqueous solution and the magnesium chloride aqueous solution were mixed in a volume ratio of 1:1, and stirred at 25°C and 500 rpm for 30 minutes under the action of a magnetic stirrer to obtain a nanoparticle mixture. At room temperature, 10 mL of the nanoparticle mixture (adjusted to pH 7.0) was mixed with 5 g / mL of Na 2 CO 3 Aqueous solution (adjusted to pH 7.0) and carbonyl reductase LsCR M6 The pure enzyme solution was mixed in equal volumes, reacted at 4°C and 500 rpm for 45 min under the action of a low-temperature magnetic stirrer to form a white flocculent precipitate, centrifuged at 5000 rpm for 5 min, and the white precipitate was washed three times with 50 mM PBS buffer (pH 7.2) to remove the unimmobilized enzyme solution and excess reaction solution. The obtained precipitate was vacuum freeze-dried at -80°C for 24 h to obtain 600 mg of carbonyl reductase LsCR M6 Nanoparticle-immobilized enzyme.
[0053] 2. Immobilized lipase PAE: Immobilize the carbonyl reductase LsCR in step 1 M6The pure enzyme solution was replaced with an equal amount of pure lipase PAE enzyme solution, and other operations were the same to obtain 600 mg of lipase PAE nanoparticle-immobilized enzyme.
[0054] Example 4: Hydrogel-immobilized enzyme
[0055] 1. Immobilized carbonyl reductase LsCR M6 :In a 10mL screw-cap bottle, add 660μL of initiator 2-hydroxyethyl methacrylate, then add 30mg of monomer N-vinyl pyrrolidone, add deionized water to make the total volume of the mixture reach 2mL, stir magnetically at 300rpm for 20min at room temperature to obtain 2mL of hydrogel prepolymer mixture, in which the final concentration of initiator is 0.1M and the final concentration of monomer is 6.08×10 -2 M; at room temperature, add carbonyl reductase LsCR to 2.0 mL of the hydrogel prepolymer mixture. M6 The pure enzyme solution is made to have a protein content of 5 mg / mL, and then 10 mg / mL of ammonium persulfate is added, and cross-linked at 4°C and 500 rpm for 45 minutes to obtain 8 mL of hydrogel loaded with carbonyl reductase, i.e., carbonyl reductase hydrogel immobilized enzyme.
[0056] 2. Immobilized lipase PAE: Immobilize the carbonyl reductase LsCR in step 1 M6 The pure enzyme solution was replaced with a pure enzyme solution of lipase PAE of equal concentration, and other operations were performed in the same manner to obtain 8 mL of hydrogel loaded with lipase PAE, i.e., lipase hydrogel immobilized enzyme.
[0057] Example 5: Enzyme immobilization using nanocomposite hydrogel
[0058] 1. Immobilized carbonyl reductase LsCR M6 :Reference Figure 1 Calcium chloride (CaCl 2 ), magnesium chloride (MgCl 2 ) were dissolved in deionized water and mixed to prepare a 5% aqueous solution. The calcium chloride aqueous solution and the magnesium chloride aqueous solution were mixed in a volume ratio of 1:1, and stirred at 25°C and 500rpm for 30min under the action of a magnetic stirrer to obtain a nanoparticle mixture. Then, 660μL of initiator methacrylate-2-hydroxyethyl ester and 30mg of monomer N-vinyl pyrrolidone were added to the nanoparticle mixture until the total amount reached 2mL, and magnetic stirring was carried out at room temperature and 300rpm for 20min to obtain 2mL of hydrogel prepolymer mixture, in which the final concentration of the initiator was 0.1M and the final concentration of the monomer was 6.08×10 -2 M; at room temperature, add 740 μL of carbonyl reductase LsCR to 2 mL of the hydrogel prepolymer mixture. M6The pure enzyme solution is prepared so that the amount of the pure enzyme solution is 2 mg / mL in terms of protein content, and then ammonium persulfate at a concentration of 10 mg / mL is added, and cross-linked at 4°C and 500 rpm for 45 minutes to obtain 8 mL of nanocomposite hydrogel loaded with carbonyl reductase. The above gel is then placed in a -80°C freeze dryer for freeze drying for 12 hours to obtain 4 g of carbonyl reductase nanocomposite hydrogel immobilized enzyme.
[0059] 2. Immobilized lipase PAE: Immobilize the carbonyl reductase LsCR in step 1 M6 The pure enzyme solution was replaced with the pure enzyme solution of lipase PAE of equal concentration, and other operations were the same to obtain 8 mL of nanocomposite hydrogel loaded with lipase PAE. The above gel was then placed in a -80°C freeze dryer for freeze drying for 12 hours to obtain 4 g of lipase nanocomposite hydrogel immobilized enzyme.
[0060] Example 6: Effect of ammonium persulfate content on the water content of nanocomposite hydrogel-immobilized enzyme
[0061] The dosage of ammonium persulfate in step 1 of Example 5 was changed to 3, 4, 5, 8, and 10 mg / mL respectively, and the other operations were the same. The equilibrium water content of the carbonyl reductase nanocomposite hydrogel immobilized enzyme prepared with different concentrations of ammonium persulfate was tested. The specific operations were as follows:
[0062] The carbonyl reductase nanocomposite hydrogel immobilized enzyme prepared with different concentrations of ammonium persulfate was placed in a small beaker, and then appropriate distilled water was added and soaked in an environment of 25°C, so that the hydrogel can fully absorb water until it reaches a state of swelling equilibrium. Then, take it out, absorb the residual water on the surface with clean filter paper, and weigh it in an electronic precision balance, which is the wet weight of the hydrogel. Then, put the weighed hydrogel sample into a clean small beaker, put the small beaker into an oven, set the oven temperature to 60°C, and vacuum dry it under this condition until the weight of the hydrogel no longer changes, that is, the hydrogel reaches a constant weight state, and then take out the dried sample, cool it to room temperature, and weigh it in an electronic balance, which is recorded as the dry weight of the hydrogel. Equilibrium water content = (hydrogel wet weight - hydrogel dry weight) / hydrogel dry weight × 100%. The results are shown in Table 1. From Table 1, it can be seen that the ammonium persulfate concentration of 10 mg / mL has a lower equilibrium water content, and the water content is <30%, and its physical bonding energy is one order of magnitude higher than that at high water content, which provides a simple method for improving the bonding properties of hydrogels.
[0063] Table 1 Effect of initiator content on water content of hydrogel
[0064]
[0065] Example 7: Determination of the loading amount of immobilized enzyme protein
[0066] The BSA (bovine serum albumin) protein quantitative analysis kit uses the biuret reaction and color reaction of protein: under alkaline conditions, protein can convert Cu 2+ Reduction to Cu + , Cu + It forms a purple complex with bicinchoninic acid (BCA) reagent, which has a strong absorption value at 562nm. Within a certain protein concentration range, the absorbance has a good linear relationship with the protein concentration. By comparing with the standard curve, the concentration of the enzyme in the washing solution can be calculated.
[0067] 1. BSA standard curve
[0068] Reagent A and reagent B in the BSA protein quantitative analysis kit of Thermo Scientific Pierce were mixed at a volume ratio of 50:1 to obtain a green clear color developer. According to Table 2, different volumes of bovine serum albumin (BSA) diluted with pure water at a concentration of 5g / L were added to the labeled reagent bottles, and then 5mL of the color developer was added to each reagent bottle, deionized water was added, and the mixture was fully mixed. The mixture was kept constant temperature in a 60°C oven for 30min, and then cooled to room temperature. The absorbance of the sample in each reagent bottle at 562nm was measured by ultraviolet spectrophotometry, and the absorbance of each sample at 562nm was subtracted from the absorbance of the blank standard (deionized water) at 562nm. The absorbance was then plotted against the corresponding BSA concentration (mg / mL) to obtain a BSA standard curve, and the curve equation was y=0.0009x+0.0068.
[0069] Table 2 Standard curve determination of protein concentration
[0070]
[0071] 2. Detection of immobilized enzyme protein loading
[0072] 5 mg of the carbonyl reductase and lipase immobilized enzymes prepared in Examples 1 to 3, 5 mL of the hydrogel immobilized enzymes of the carbonyl reductase and lipase prepared in Example 4, and 5 mg of the nanocomposite hydrogel immobilized enzymes of the carbonyl reductase or lipase prepared in Example 5 were added to 5 mL of deionized water, soaked at room temperature for 20 h, the immobilized enzymes were taken out, and the respective washing liquids were collected.
[0073] 0.5 μL of the washing solution was added to 0.5 μL of deionized water, and then 5 μL of the color developer in step 1 was added. The mixture was kept at a constant temperature of 60°C for 30 min, and then cooled to room temperature. The ultraviolet absorbance at 562 nm was measured by ultraviolet spectrophotometry. The enzyme concentration in the washing solution was obtained according to the BSA standard curve, and the immobilized enzyme protein loading was calculated. The results are shown in Table 3 and Figure 3 shown.
[0074] Table 3 Immobilized enzyme protein loading
[0075]
[0076] As shown in Table 3, when different carriers are used in Examples 1-5, the protein loading amount is different. The use of nanocomposite hydrogel in Example 5 can increase the loading amount, and the negatively charged enzyme protein is enriched on the positively charged nanoparticle carrier through the charge effect, which increases the physical force, and forms a three-dimensional network structure through the polymerization method, so that the carbonyl reductase and lipase are fixed inside the hydrogel.
[0077] Figure 3 is a bar graph showing the protein loading of carbonyl reductase immobilized enzyme, silica (SiO 2 ) represents the carbonyl reductase immobilized enzyme prepared by the method of Example 1, liposome (Lipo) represents the carbonyl reductase immobilized enzyme prepared by Example 2, hydrogel (pHEMA) represents the carbonyl reductase hydrogel immobilized enzyme prepared by Example 4, nanoparticles (CaMg(CO 3 ) 2 ) Representative Example 3 Preparation of carbonyl reductase immobilized enzyme, nanocomposite hydrogel (pHEMA-CaMg (CO 3 ) 2 ) represents the nanocomposite hydrogel-immobilized enzyme of carbonyl reductase prepared in Example 5. Figure 3 It can be seen that compared with the use of nanocomposite hydrogel pHEMA-CaMg(CO 3 ) 2 Loading relative to SiO 2 、Lipo、CaMg(CO 3 ) 2 , pHEMA is more stable, with a maximum loading rate of 3422 mg / g.
[0078] The results show that the reaction conditions of the method in Example 5 are mild and have almost no denaturation effect on the loaded enzyme protein. While ensuring the activity of the enzyme, it solves the problem of easy leakage of enzymes immobilized by traditional embedding materials.
[0079] Example 8. Characterization of particle size and pore size of immobilized enzyme
[0080] The average particle size is an important indicator for evaluating the quality of nanocarrier systems. The particle size and distribution directly affect the physical stability of the nanodispersion system, and the potential of the nanodispersion system determines whether the particles in the liquid are stable or tend to flocculate. As an instrument mainly used to study the particle size composition, the nano-laser particle size analyzer can provide three characteristics of particles or macromolecules in the liquid medium, namely particle size, potential, and molecular weight. It is one of the commonly used evaluation methods for preparations, with the advantages of wide dynamic range of measurement, fast measurement speed, convenient operation, wide application range, and high reliability.
[0081] 1. Particle size characterization of immobilized enzyme
[0082] Take 10 mg of the immobilized enzyme of carbonyl reductase prepared in Examples 1 to 5, mix with 10 mL of ultrapure water, and filter with a 0.45 μm microporous filter membrane. Dilute the filter cake with ultrapure water at an amount of 5 g / mL. Then, after 30 minutes of ultrasound at 100 W, take 2 mL and transfer it to the quartz cuvette of the nano laser particle size analyzer (Nano-ZS90X). After standing at 25°C for 30 seconds, measure the particle size. Each sample is scanned 3 times to calculate the average value. The particle size prepared in Example 1 is 80 nm, the particle size prepared in Example 2 is 130 nm, the particle size prepared in Example 3 is 260 nm, the particle size prepared in Example 4 is 790 nm, and the particle size prepared in Example 5 is 820 nm. The particle sizes of the immobilized carbonyl reductase enzymes prepared by the methods of Examples 3, 4 and 5 are shown in Table 1. Figure 4 , Figure 4 It can be seen that the size of the immobilized enzyme prepared using the composite hydrogel is comparable to that of the hydrogel used alone.
[0083] 2. Characterization of surface area and pore properties of immobilized enzymes
[0084] The BET method was used to measure the N 2 Gas adsorption isotherms are used to obtain the specific surface area and pore size distribution information of the material.
[0085] (1) Sample pretreatment
[0086] First, the sample tube was carefully cleaned and dried, and then the mass of the empty sample tube was weighed using an analytical balance, and then 100 mg of the immobilized enzyme of the carbonyl reductase prepared in Example 1-5 was taken and placed in the sample tube.
[0087] (2) Isothermal adsorption experiment
[0088] Using nitrogen as the adsorbent, the sample tube of step (1) was installed on the degassing station of the BET specific surface area and pore size analyzer. The instrument will initialize the pipeline again, the Dewar flask will rise and automatically adjust the height, and degas for 30 minutes at a degassing temperature of 150°C and different pressures (relative pressure P was set to 0.2, 0.4, 0.6, and 0.99, respectively). The relative pressure (P / P 0 ) is the horizontal axis, and the volume of the adsorbate adsorbed by unit weight of solid adsorbent under constant temperature is the vertical axis, and the adsorption equilibrium isotherm is drawn. P is the true pressure of the gas, P 0 is the saturated vapor pressure of the gas at the measurement temperature. Based on the adsorption equilibrium isotherm, the specific surface area, pore volume, pore width and average pore size were calculated using the BET formula, and the results are shown in Table 4. The adsorption equilibrium isotherms of the immobilized carbonyl reductase prepared by the methods of Examples 3, 4 and 5 are shown in Table 4. Figure 5 As shown, the hydrogel-immobilized enzyme represents the carbonyl reductase immobilized enzyme prepared in Example 4, the nanoparticle-immobilized enzyme represents the carbonyl reductase immobilized enzyme prepared in Example 3, and the nanocomposite hydrogel-immobilized enzyme represents the carbonyl reductase immobilized enzyme prepared in Example 5.
[0089] Based on the BET results, the specific surface area and pore volume of the immobilized carbonyl reductase prepared by the methods of Examples 3, 4 and 5 were calculated. Figure 6 and Table 4 , compared with hydrogels and nanoparticles, the composite hydrogel has a larger specific surface area and pore volume.
[0090] Table 4 Surface area and pore properties of immobilized enzymes on different carriers
[0091]
[0092] As shown in Table 4, the specific surface area of the immobilized enzyme prepared by the nanocomposite hydrogel in Example 5 is about 3100 m 2 / g, pore volume is 2.43cm 3 / g. Compared with the silica carrier of Example 1, the liposome carrier of Example 2, the nanoparticle carrier of Example 3 and the hydrogel carrier of Example 4, the nanocomposite hydrogel carrier of Example 5 significantly increases the pore volume, specific surface area, average pore size and pore width of the immobilized enzyme, and the appropriate pore size and pore volume are conducive to promoting the accessibility of the substrate to the active site of the enzyme.
[0093] Example 9: Effect of immobilization time on enzyme immobilization efficiency
[0094] The enzyme loading was determined by the Coomassie brilliant blue method to measure the protein content.
[0095] 1. Carbonyl reductase The cross-linking reaction time at 4°C and 500 rpm during the immobilization of carbonyl reductase in Examples 3, 4, and 5 was set to 100 min. Samples were taken at 15, 30, 45, 60, and 90 min during the reaction. The protein adsorption amount was detected by the method of Example 7. The enzyme loading rate was calculated according to Formula 1. The results are shown in Table 1. Figure 7 .
[0096]
[0097] Figure 7 This indicates that 45 min is the optimal fixation time.
[0098] 2. Lipase
[0099] The cross-linking reaction time at 4°C and 500 rpm during the lipase immobilization process of Examples 3, 4, and 5 was set to 100 min. Samples were taken at 5, 15, 30, 45, 60, 75, and 90 min during the reaction. The protein adsorption amount was detected by the method of Example 7. The enzyme loading rate was calculated according to Formula 1. The results are shown in Table 1. Figure 8 .
[0100] Figure 8 This indicates that 45 min is the optimal fixation time.
[0101] Example 10: Determination of immobilized enzyme activity
[0102] 1. Immobilized carbonyl reductase activity test
[0103] Immobilized carbonyl reductase catalyzes hydrolysis reaction: 400 μL of 30 g / L substrate 2-chloro-1-(3,4-difluorophenyl) ethyl ketone isopropanol solution, 500 μL of 0.1M, pH 6.0 citric acid buffer solution, and then 6 mg of carbonyl reductase nanocomposite hydrogel immobilized enzyme prepared in Example 5 and NADPH are added to form a 1 mL reaction system, the substrate is added to a final concentration of 15 g / L, the final concentration of isopropanol volume is 40%, the catalyst is added to a final concentration of 6 g / L, and NADPH is added to a final concentration of 20 mM, and the catalytic reaction is carried out at 35 ° C and 1000 rpm for 15 min. After the reaction is completed, the reaction solution is centrifuged to obtain a supernatant and a precipitate. The precipitate is washed 3 times with 0.1 M, pH 7.2 potassium phosphate buffer, and the immobilized carbonyl reductase is recovered and put into the next batch of reactions again. The conditions for each batch of reactions are the same. 1 mL of ethyl acetate is added to the supernatant, fully shaken, and centrifuged at 12000 rpm for 2 min. A small amount of anhydrous sodium sulfate was added to the supernatant to remove residual water, and then gas chromatography was performed to determine the content of the product (1S)-2-chloro-1-(3,4-difluorophenyl)ethanol.
[0104] The enzyme activity was defined as: one unit (U) of enzyme activity was the amount of immobilized carbonyl reductase required to convert 1 μmol of substrate into product per minute in 0.1 M, pH 6.0 citric acid buffer solution at 30°C.
[0105] The specific activity of the immobilized carbonyl reductase is defined as follows: the enzyme activity per unit mass of the immobilized carbonyl reductase, expressed as U / g.
[0106] Gas phase detection conditions were as follows: Agilent (8890) gas chromatograph was used for detection, GC (BGB-174, 30m×0.25mm, 0.25μm). The injector and detector were set at 250°C and 250°C respectively, the column temperature was set at 160°C and maintained for 15 min, the split ratio was 30:1, the injection volume was 2μL, and other conditions were the default detection conditions.
[0107] The enzyme activity test of free carbonyl reductase is the same as that of immobilized enzyme.
[0108] 2. Immobilized lipase activity test
[0109] Immobilized lipase hydrolysis substrate reaction: 40 μL of PB buffer solution (pH 7.0) with a concentration of 15 g / L substrate p-nitrophenyl phosphate (p-NPP) was added to a 96-well reaction plate system, 50 μL of PB buffer solution (pH 7.0), and then 1.2 mg of the lipase nanocomposite hydrogel immobilized enzyme prepared in Example 5 was added to form a 0.1 mL reaction system, the substrate was added to a final concentration of 30 g / L, and the catalyst was added to a final concentration of 12 g / L, and the catalytic reaction was carried out at 30 ° C and 200 rpm for 10 min. After the reaction was completed, the reaction solution was centrifuged to obtain a supernatant and a precipitate, and the precipitate was washed 3 times with a pH 7.2 PBS buffer solution, and the immobilized lipase was recovered and put into the next batch of reactions again, and the conditions for each batch of reactions were the same. The supernatant was detected by an ELISA instrument for absorbance at 405 nm, and the p-nitrophenol content in the supernatant was obtained according to the p-nitrophenol standard curve, and the enzyme activity was calculated.
[0110] The enzyme activity of the immobilized lipase is defined as follows: at 30°C, in a 0.1 M, pH 7.0 buffer solution, the amount of immobilized lipase required to convert 1 μmol of the substrate p-nitrophenyl phosphate into the product p-nitrophenol per minute is one enzyme activity unit (U).
[0111] The specific activity of the immobilized enzyme is defined as follows: the enzyme activity per unit mass of the immobilized lipase hydrogel, expressed as U / g.
[0112] The enzyme activity test of free lipase is the same as that of immobilized enzyme.
[0113] Example 11: Effect of temperature on free enzyme / immobilized enzyme activity
[0114] Optimum temperature of free enzyme / immobilized carbonyl reductase: The reaction temperature of 35°C in step 1 of Example 10 was adjusted to 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80°C respectively, and other operating conditions remained unchanged. The experiment was repeated 3 times at each temperature. The relative enzyme activity at the optimal temperature was taken as 100%, and the relative enzyme activity was calculated according to formula (2). The results are shown in Fig. 9 At 30°C, the free carbonyl reductase and the immobilized enzyme showed a steady and slow rising trend, and the relative activity of the immobilized enzyme was higher than that of the free enzyme; at 50°C, the free carbonyl reductase and the immobilized enzyme showed a rapid falling trend. The temperature exceeded the tolerance range of the carbonyl reductase, which led to a rapid decline in enzyme activity. However, the relative activity of the immobilized enzyme was still higher than that of the free carbonyl reductase.
[0115] Optimum temperature of free enzyme / immobilized lipase: The reaction temperature of 30°C in step 2 of Example 10 was changed to 20, 25, 30, 35, 40, 45, 50, 55, 60°C, and other operating conditions remained unchanged. The experiment was repeated 3 times at each temperature. The relative enzyme activity at the optimal temperature was taken as 100%, and the relative enzyme activity was calculated according to formula (2). The results are shown in Fig.10 Starting from 20℃, the relative activity of immobilized lipase decreased more slowly than that of free lipase, indicating that the temperature tolerance of immobilized enzyme was higher than that of free enzyme and the carrier played a protective role on the enzyme.
[0116]
[0117] Example 12: Effect of pH on the activity of free enzyme and immobilized enzyme
[0118] 1. Free enzyme / immobilized carbonyl reductase
[0119] The pH 6.0 in step 1 of Example 10 was changed to different pH buffers (pH 3.0-10.0), specifically: 50 mM sodium citrate buffer (pH 3.0-6.0), 50 mM potassium phosphate buffer (pH 6.0-8.0), 50 mM Tris-HCl buffer (pH 8.0-10.0). Other operating conditions were the same, and the highest enzyme activity under different pH conditions was defined as 100%, and the relative activity percentage was calculated. The results are shown in Fig.11 .
[0120] 2. Free enzyme / immobilized lipase
[0121] The pH 7.0 in step 2 of Example 10 was changed to different pH buffers (pH 3.0-11.0), specifically: 50 mM sodium citrate buffer (pH 3.0-5.0), 50 mM sodium phosphate buffer (pH 6.0-8.0), 50 mM Tris-HCl buffer (pH 9.0) and 50 mM Na 2 CO 3 -NaHCO 3 (pH 10.0~11.0). Other operating conditions were the same, and the highest enzyme activity under different pH conditions was defined as 100%. The relative activity percentage was calculated. The results are shown in Fig.12 .
[0122] Free carbonyl reductase showed higher activity at pH 6.0, and free lipase showed higher activity at pH 7.0. For immobilized enzymes, the optimal pH of immobilized carbonyl reductase did not change, while immobilized lipase showed higher activity at pH 8.0 (relative activity greater than 80%). Compared with free enzymes, the optimal pH of immobilized enzymes was higher, which may be due to the fact that the nanocomposite hydrogel changed the local microenvironment of the co-immobilized enzyme catalysis, causing the optimal pH to shift slightly toward alkalinity. Therefore, we took pH 6.0 as the optimal reaction condition for immobilized carbonyl reductase and pH 8.0 as the optimal reaction condition for immobilized lipase.
[0123] Example 13: Effect of the number of cycles on the immobilized enzyme
[0124] 1. Carbonyl reductase
[0125] The enzymatic activity of the immobilized carbonyl reductase prepared in Examples 4 and 5 was detected by the method of Step 1 of Example 10. The immobilized enzyme was detected 10 times in a cycle. Fig.13 . As can be seen from the figure, the specific enzyme activity of the immobilized enzyme in the initial reaction is 34.9U / mg. During the first four cycles, the enzyme activity of the nanocomposite hydrogel immobilized enzyme remained consistent with the enzyme activity of the initial reaction. The specific enzyme activity of the immobilized enzyme after 10 cycles decreased day by day, but the nanocomposite hydrogel immobilized carbonyl reductase could still maintain 64.2% of the initial enzyme activity after 10 cycles. At the 10th cycle, the enzyme activity of the hydrogel immobilized carbonyl reductase was only 15% of the initial enzyme activity, proving that the conventional method of immobilizing the enzyme will have unstable activity and is easily inactivated at room temperature. The nanocomposite hydrogel immobilized enzyme carrier has a good protective effect on the carbonyl reductase, reducing the influence of external factors on the active site of the carbonyl reductase. Therefore, the nanocomposite pHEMA-CaMg(CO 3 ) 2 Has good recycling performance.
[0126] 2. Lipase
[0127] The enzymatic activity of the immobilized lipase prepared in Example 4 and Example 5 was detected by the method of step 2 of Example 10. The immobilized enzyme was detected 10 times in a cycle. Fig.14 .
[0128] The nanocomposite hydrogel-immobilized lipase can still maintain 70% of the initial enzyme activity after 10 cycles, which shows that immobilized enzymes have a good market prospect.
[0129] Example 14: Fourier transform infrared spectroscopy characterization of immobilized enzymes after using different batches
[0130] The immobilized carbonyl reductase prepared by the method of Example 5 using different batches (0, 3, 6, 9, 10) of Example 13 was analyzed by Fourier transform infrared spectrometer (FTIR) (Nicolet 6700 FTIR-ATR, ThermoFisher Scientific, USA) at 1 cm -1 Wave number resolution characterizes FTIR spectra, the results are shown in Fig.15 .
[0131] Fig.15 The infrared spectrum (FT-IR) graph showed that the peaks of the spectrum and its second-order derivatives were basically the same as those before use, indicating that the nanocomposite hydrogel pHEMA-CaMg(CO 3 ) 2 The secondary structure of the immobilized enzyme was well preserved. After using different batches of immobilized enzyme, there was an obvious amide II band, and the immobilized enzyme after 10 batches still had an amide II band, so it can be judged that the enzyme can be effectively immobilized in the nanocomposite hydrogel and can carry out catalytic reactions.
[0132] In summary, the immobilization reaction conditions of the nanocomposite hydrogel of the present invention are mild, and the three-dimensional conformation of carbonyl reductase and lipase will not be affected, thereby ensuring the activity of the enzymes. At the same time, the present invention solves the problem of easy leakage of immobilized enzymes by the embedding method. Through the action of charge, the negatively charged enzyme protein is enriched on the positively charged nanoparticle monomers, thereby increasing the physical force. Moreover, through the polymerization method, a three-dimensional network structure is formed, so that the carbonyl reductase and lipase are fixed inside the hydrogel.
[0133] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing immobilized enzyme using nanocomposite hydrogel, characterized in that: The method comprises the following steps: (1) mixing a calcium chloride aqueous solution and a magnesium chloride aqueous solution, and stirring them at 20 to 30° C. and 300 to 600 rpm for 30 minutes under the action of a magnetic stirrer to obtain a nanoparticle mixed solution; (2) adding an initiator and a monomer to the nanoparticle mixture, and then adding deionized water, and magnetically stirring at 20 to 30° C. and 200 to 400 rpm for 10 to 30 minutes to obtain a hydrogel prepolymer mixture; the initiator includes 2-hydroxyethyl methacrylate; and the monomer includes N-vinyl pyrrolidone; (3) At room temperature, enzyme solution is added to the hydrogel prepolymer mixture, and then ammonium persulfate is added, and cross-linking is performed at 20-35° C. and 300-600 rpm for 1-100 min to obtain an enzyme-loaded nanocomposite hydrogel, and freeze-dried at -80° C. for 12 h to obtain a nanocomposite hydrogel immobilized enzyme.
2. The method according to claim 1, characterized in that Step (1) Calcium chloride and magnesium chloride are dissolved in deionized water respectively and mixed to prepare an aqueous solution with a mass fraction of 5%; the calcium chloride aqueous solution and the magnesium chloride aqueous solution are mixed in a volume ratio of 1:
1.
3. The method according to claim 1, characterized in that In step (2), the final concentration of the initiator in the hydrogel prepolymerization mixture is 0.05-0.5 M, and the final concentration of the monomer is 0.1-1.0 mM.
4. The method according to claim 1, characterized in that The enzyme solution in step (3) includes pure enzyme solution of carbonyl reductase or pure enzyme solution of lipase, and the amount of the pure enzyme solution is 1 to 6 g / L in terms of protein content.
5. The method according to claim 1, characterized in that In step (3), the concentration of ammonium persulfate added is 3 to 10 mg / mL based on the volume of the hydrogel prepolymerization mixture.
6. The method according to claim 1, characterized in that Step (3), cross-linking at 25°C and 500 rpm for 45 min.
7. Use of the immobilized enzyme prepared by the method of claim 1 in catalyzing the preparation of drug intermediates from ketone compounds or ester compounds.
8. The use according to claim 7, characterized in that The method for preparing a drug intermediate by using an immobilized enzyme to catalyze a ketone compound comprises: using a nanocomposite hydrogel immobilized enzyme containing a carbonyl reductase as a catalyst, using a ketone compound as a substrate, using isopropanol as a cosubstrate, using NADPH as a coenzyme, and using a buffer solution with a pH of 3.0-10.0 as a reaction medium to form a conversion system, reacting at 30-80° C. and 1000 rpm, and after the reaction is completed, extracting, separating, and purifying the reaction liquid with ethyl acetate to obtain a chiral aromatic alcohol; the ketone compound is 2-chloro-1-(3,4-difluorophenyl)ethanone, and the corresponding chiral aromatic alcohol is (1S)-2-chloro-1-(3,4-difluorophenyl)ethanol.
9. The use according to claim 7, characterized in that The method for preparing a drug intermediate by using an immobilized enzyme to catalyze an ester compound is as follows: using a nanocomposite hydrogel containing lipase as an immobilized enzyme as a catalyst and using an ester compound as a substrate; The conversion system is formed by using a buffer solution of pH 3.0-11.0 as a reaction medium, and the reaction is carried out at 20-60° C. and 1000 rpm; The ester compound is p-nitrophenyl phosphate, and the corresponding product is p-nitrophenol.
Citation Information
Cited By
Sustainable enzyme-loaded hydrogel based on heterodimer alpha-helix induced self-assembly
CN120384073A
